An exploratory study highlighting the complexities in the targeting of beneficiaries in Malawi's social cash transfer programme - Mwanza, Desire (Department of Sociology, 2021)
“The rise of social protection in form of social safety nets is attributed to the forceful return of poverty onto the international development agenda credited to World Bank and the United Nations Development Programme (UNDP)” (Chisinga, 2007:3). The basis of the discussion of social protection as a new model for development derives from the vision of the initiative as a path to sustainable economic development due to its holistic approach to poverty eradication and capability deprivation (Taylor, 2008)."In Africa, where pre-existing welfare regimes are often absent or comparatively very weak, the origins of cash transfer schemes stem from the search for alternatives to food and input transfers to tackle hunger"(Slater,2011:256). In the sub-Saharan region, for example, countries such as South Africa, Zambia, Kenya, Namibia and Malawi have similarly embraced the trend by adopting social grants and cash transfers as a solution to poverty and capability deprivation. Malawi, portrays a vivid image of a country with little resources for 17 million inhabitants, leaving more than half of the population below the poverty line (Malawi Growth and Development Strategy (MDGS) III report (2017). The goal of the Malawi Social Cash Transfer Program (SCTP) is to reduce poverty, hunger and increase school enrolment among the poorest 10% of households. Targeting the correct 10% is key to the success of the program. The World Bank Group, Malawi Poverty Assessment (2016), calls into question the likelihood of precisely targeting the chronically poor people in such initiatives. On the other hand, Houssou et al., 2007 and Slater, 2011 insist on the need to evaluate the foresee-ability of contextual intervention programs, especially if a country does not have the capacity for widespread social grants as targeting becomes a matter of concern. The idea is that social cash transfers will be successful in reducing poverty if the right individuals are targeted. Considering the high poverty rate in Malawi and the gaps between the lower poverty deciles and the income profile are marginal (Ellis, 2008), how accurate is the decentralized targeting process? Based on this rationale, this exploratory research explored and highlights the complexities in targeting of beneficiaries in the program which, as a result has contributed to the derailment of the program. Findings show that the Government of Malawi (GoM) has overlooked the necessary control mechanisms to achieve effective targeting. As such, the study identifies anomalies in the targeting process that play a significant role in affecting the achievement of the goal of the program. Thus, SCTP falls short of combating poverty in a multi-dimensional manner.